Strategi Guru dalam Mendorong Minat Belajar Siswa dalam Pembelajaran Pendidikan Jasmani Olahraga dan Kesehatan Setelah Pandemi Covid-19 Tingkat SMPN di Kota Palu - Sulastri, Cici; Nasuka, Nasuka; Setyawati, Heny (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2024)
This research aims to determine teachers' strategies for encouraging students' interest in learning PJOK after the COVID-19 pandemic. The method used in this research uses a qualitative descriptive approach with a case study design. Data collection techniques were carried out using observation, interviews, and documentation. Data and data sources were obtained from primary and secondary data. Primary data for all PJOK teachers at SMPN Palu City. Secondary data was obtained from document data at SMPN Palu City. Research Results on Teacher Strategies to Increase Students' Interest in Learning After the COVID-19 Pandemic, the teacher's way of finding out the level of student's knowledge in the lessons that have been taught uses three methods; the first is the question and answer method, the second is giving written tests, the third is conducting sports practice tests. Secondly, students' readiness, interest, and engagement in PJOK learning after the COVID-19 pandemic; the media used in learning uses an audiovisual projector to display PJOK learning to support existing learning plus other supporting tools that can be used in practical learning. The conclusion is that the teacher's strategy to increase students' interest in learning is carried out. The teacher's strategy to increase students' interest in learning has been implemented through a directed and planned learning program in the excellent category. Keywords: Covid 19, interest in learning, teacher strategies